Value chain analysis of turmeric- a study with special reference to - Rahana P Ibrahim (College of co-operation, banking and management, 2014)
Value chain refers to the full range of activities that are required to bring a product (or a service) from conception, through the different phases of production, to delivery to final consumers and disposal after use. Mapping is the process of making a pictorial representation of the VCA (value chain analysis). The study was conducted with the objective of to map the different components and stakeholders in the value chain of numeric to analyse the distribution of benefits at each level of value chain of turmeric. The study was based upon both primary and secondary sources of data. Primary data was collected through the survey of farmers, village traders, wholesalers, and input suppliers. Secondary data were collected from the published works of various authors, several journals and magazines. The collected data were analysed by using the tools like Value chain mapping, Percentage Analysis and rank order scale.